DIGITAL LITERACY AS A FUNDAMENTAL SKILL IN MODERN ECONOMIC EDUCATION: A LITERATURE REVIEW - Abdurrahim (Formad English Foundation NTB Jakarta, 2025)
This study aimed to analyze the role of digital literacy as a fundamental skill in modern economic education. Amid the rapid advancement of digital technology, digital literacy was considered an essential competence that supported students in understanding and applying economic concepts effectively. The primary objective of this research was to identify the relationship between digital literacy and the development of economic skills in the digital era. The research method employed was a qualitative approach using a literature review design. Data were obtained through the selection of relevant literature, including journal articles, books, and research reports published between 2012 and 2024. Data analysis was conducted using thematic analysis techniques, which involved identifying key themes related to digital literacy in economic education. The findings indicated that digital literacy played a significant role in enhancing students’ economic skills, particularly in accessing and analyzing economic data. This study also revealed that the integration of technology in economic education improved students’ understanding of economic theory and better prepared them to face the challenges of the digital economy. In conclusion, digital literacy should be an integral part of the economic education curriculum. This study made a significant contribution to the development of digital literacy as a foundational competence supporting economic learning and opened opportunities for further in-depth research on the impact of digital literacy on economic education.